ANALISIS TECHNOLOGY ACCEPTANCE MODEL GENERASI MILLENIAL JAKARTA TERHADAP PENGGUNAAN E-MONEY - Sultan, Randy Ramanda; Haryanti, Tuti; Kurniawati, Laela (LPPM Universitas Nusa Mandiri, 2019)
The development of Digital Technology that has penetrated almost all lines of human life In the field of Finance e-money is considered to have many benefits, mostly because of the simplicity factor in using it. Bank Indonesia as the authority in charge of finance also launched Non-Cash Movement and conducted socialization-socialization to various layers of society. However, although socialization has been done, the acceptance of e-money in Indonesia is still low. Based on previous research, there are many factors that can influence the high acceptance and use of technology, among others, the perception of risk and Facilitating condition. This research was conducted to find out the influence of both external factors to the use of electronic money among Jakarta millennial society conducted by testing the influence of these factors using approach Technology Acceptance Model (TAM). Subjects in this study amounted to 100 people. Data collection is done by distributing the online questionnaire. Data analysis using SPSS for Windows version 16.0. Based on the research result, it is found that the two external factors have an effect on the acceptance of e-money.